Immunohistochemical and molecular characterizations in urothelial carcinoma of bladder in patients less than 45 years - Weyerer, Veronika; Schneckenpointner, Roland; Filbeck, Thomas; Burger, Maximilian; Hofstaedter, Ferdinand; Wild, Peter J.; Fine, Samson W.; Humphrey, Peter A.; Dehner, Louis P.; Amin, Mahul B.; Rueschoff, Josef; Boltze, Carsten; et al. (Journal of Cancer, 2017)
Bladder tumours in early-onset patients are rare and seem to exhibit unique clinicopathological features. Only few studies have investigated somatic alterations in this specific age of onset group and evidence is accumulating of a distinct molecular behaviour of early-onset bladder tumours. We collected the largest cohort of early-onset tumours of patients 45 years old or younger and aimed to test genomic alterations typically found in bladder cancer. Tumours of 118 early-onset patients were compared with a consecutive group of 113 cases. Immunohistochemistry of TP53, CK20 and Ki-67 was carried out. Molecular analysis was conducted to test for loss of heterozygosity of chromosome 9 and 17, as well as TP53 and FGFR3 mutations. Fisher´s exact and chi-squared test were appropriately used. No differences in grade/stage characteristics were observed. Overexpressed TP53 was differentially distributed between the two groups. TP53 nuclear accumulation was significantly more frequent in early-onset papillomas, PUNLMPs and pTa low-grade tumours compared to the consecutive cohort (p=0.005). Moreover, chromosome 9 deletions (29.5% vs. 44.6%) and FGFR3 mutations (34.5% vs. 63.7%) were less often detected in early-onset patients (p=0.05 and p<0.0001). By comparing the largest cohort of early-onset bladder cancer patients with an unselected group, we demonstrated that the typical molecular features are not independent of age at diagnosis. Our study supports the hypothesis of a distinct biological behaviour in early-onset tumours.
EVALuna2:6841